Antimicrobial Effect of Formononetin Against the Periodontal Pathogens Enterococcus faecalis and Candida albicans - Delfan, Negar; Moghadam, Maryam Dalaei; Shakib, Pegah; Sepahdar, Asma; Naghibeiranvand, Zahra (Recent Patents on Biotechnology, 2026)
BackgroundAmong the bioactive isoflavones identified from different plants is formononetin. Formononetin's antioxidant, anti-inflammatory, and anti-cancer qualities have all received a lot of attention lately. The goal of the current investigation was to examine formononetin's antifungal and antibacterial activity against Candida albicans and Enterococcus faecalis in vitro, respectively.MethodsThe present study determined the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and Minimum Fungicidal Concentration (MFC) of formononetin, chlorhexidine, formononetin + chlorhexidine, Formononetin + nystatin, and nystatin against E. faecalis and C. albicans isolates. Next, SPSS version 25 was used to analyze the data. A significance cutoff of P<0.05 was taken into account.ResultsChlorhexidine + formononetin and formononetin alone had the greatest and lowest minimum inhibitory concentrations (MIC) against E. faecalis, at 6.6 and 18.3 μg/ml, respectively. With MIC values of 0.66 and 8.3 μg/ml against a C. albicans isolate sensitive to nystatin, the combination of formononetin + nystatin and formononetin alone was shown to have the greatest and lowest anti-candida effects.ConclusionThe findings demonstrated a considerably greater antibacterial effect (P<0.05) for the combinations of formononetin + nystatin and chlorhexidine as compared to nystatin and chlorhexidine alone.
Keywords: Antimicrobial effects